Clinical role of filgrastim in the management of patients at risk of prolonged severe neutropenia: An evidence‐based review. Issue 11 (13th September 2019) - Bongiovanni, Alberto; Recine, Federica; Fausti, Valentina; Rossi, Benedetta; Mercatali, Laura; Liverani, Chiara; De Vita, Alessandro; Gurrieri, Lorena; De Bonis, Silvia; Miserocchi, Giacomo; Spadazzi, Chiara; Calpona, Sebastiano; et al.
Abstract: Background: Patients undergoing chemotherapy are at risk of toxicity, especially of haematological origin. Granulocyte depletion, although often underestimated, can lead to the occurrence of an event defined as febrile neutropenia (FN). Neutropenic fever syndromes are dangerous because they cause major complications in around 25%‐30% of patients and have a mortality rate of up to 11%. Treatment for FN was limited to antibiotics and supportive therapies until filgrastim was approved for use in the 1990s. Objectives: The present systematic review focuses on the efficacy and safety of this haematopoietic growth factor. Data Sources and Methods: For this review, a systematic literature search of electronic databases and references from recent reviews up to December 2018 was carried out to identify clinical trials, observational studies and case reports evaluating filgrastim efficacy and safety. English language was defined as a restriction. Published randomised controlled trials (RCTs), case reports and reviews analysing the effects of filgrastim on severe neutropenia and its limits were considered. Four review authors independently selected the studies, assessed the risk of bias and extracted study data. Results: As reported in ASCO guidelines, the efficacy of filgrastim with respect to placebo or no treatment in RCTs is based on its prevention of FN. A recent meta‐analysis analysed nine RCTs with 2197 patients, revealing a reduction in the incidence of FN with filgrastim (risk ratio [RR] 0.63, 95% CI 0.53‐0.75). These findings were further confirmed in two observational studies. Bone pain is the most commonly reported adverse event with filgrastim, while other toxicities are associated with filgrastim efficacy and with an increased neutrophil count. Key Findings: In conclusion, our findings attest to the previous results on the efficacy and safety of filgrastim.